The little book of sand and water : ideas for activities for the foundation stage - Featherstone, Sally; Evans, Michael (London : Featherstone, 2014)
Give your sand and water sessions a new lease of life with this fully updated Little Book. Split into two sections, it offers a range of activities for sand and water play that link to the early learning goals and which are accompanied by a list of suggested resources, useful vocabulary and related songs and stories to take the theme further.
Keywords: Early childhood education -- Activity programs -- Great Britain; Educational games; Outdoor education